Analysis Of Marketing Strategy Success In PT. Indofood - Suhairi; Mutia Sari; Layla Nurul Sakinah; Raudah Azahra Manurung (CV. AFDIFAL MAJU BERKAH, 2023)
The success of a company also certainly lies in the distribution or marketing of the products produced. Marketing management plays an active role in analyzing the strategies to be used. To achieve efficient and effective organizational goals, marketing management is an effort that involves planning, executing (which includes organizing, directing, and coordinating) and supervising or organizing marketing operations within an organization. This study aims to analyze whether the strategies undertaken by PT. INDOFOOD has successfully or not penetrated the global market. The method used in this study is qualitative, namely through literature or literature review, namely research sourced from books, scientific journals, newspapers, and others. The results showed that PT. INDOFOOD has successfully conducted marketing, both marketing to local and global markets. This is evidenced by the expansion of factories abroad and the company's revenue is increasing every year.